Longitudinal bone mineral content and density in Rett syndrome and their contributing factors - Jefferson, Amanda; Fyfe, Sue; Downs, Jennepher; Woodhead, H.; Jacoby, P.; Leonard, H. (Elsevier Inc., 2015)
Bone mass and density are low in females with Rett syndrome. This study used Dual energy x-ray absorptiometry to measure annual changes in z-scores for areal bone mineral density (aBMD) and bone mineral content (BMC) in the lumbar spine and total body in an Australian Rett syndrome cohort at baseline and then after three to four years. Bone mineral apparent density (BMAD) was calculated in the lumbar spine. Annual changes in lean tissue mass (LTM) and bone area (BA) were also assessed. The effects of age, genotype, mobility, menstrual status and epilepsy diagnosis on these parameters were also investigated. The baseline sample included 97 individuals who were representative of the total live Australian Rett syndrome population under 30 years in 2005 (n = 274). Of these 74 had a follow-up scan. Less than a quarter of females were able to walk on their own at follow-up. Bone area and LTM z-scores declined over the time between the baseline and follow-up scans. Mean height-standardised z-scores for the bone outcomes were obtained from multiple regression models. The lumbar spine showed a positive mean annual BMAD z-score change (0.08) and a marginal decrease in aBMD (− 0.04). The mean z-score change per annum for those ‘who could walk unaided’ was more positive for LS BMAD (p = 0.040). Total body BMD mean annual z-score change from baseline to follow-up was negative (− 0.03). However this change was positive in those who had achieved menses prior to the study (0.03, p = 0,040). Total body BMC showed the most negative change (− 0.60), representing a decrease in bone mineral content over time. This normalised to a z-score change of 0.21 once adjusted for the reduced lean tissue mass mean z-score change (− 0.21) and bone area mean z-score change (− 0.14).Overall, the bone mineral content, bone mineral density, bone area and lean tissue mass z-scores for all outcome measures declined, with the TB BMC showing significant decreases. Weight, height and muscle mass appear to have impacts on bone formation and we recommend that nutritional intake should be closely monitored and a physical activity plan developed to optimise bone health. Pubertal progression should also be assessed in conjunction with serial densitometry assessments to track bone mass and density changes over time.